2015
DOI: 10.4168/aard.2015.3.2.116
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of allergic rhinitis in Korean children

Abstract: Purpose: The characteristics of allergic rhinitis can be different among countries and areas because causative allergens and aggravating factors depend on the living environment. However, there have been few studies on the clinical feature of Korean children with allergic rhinitis, as well as on clinical characteristics in different age groups. The aim of this study was to investigate the clinical characteristics of Korean children with allergic rhinitis. Methods: The medical records of children under 12 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
1
1
1
1
Order By: Relevance
“…A Norwegian study reported a 72.8% prevalence of AR and 27.2% of NAR in 10 year-olds 7. A Korean study reported 76.9% AR vs 23.1% NAR 21. The prevalence reported in our study may be different those in from other studies due to not having inhalant allergen test data from all patients, particularly ≤5 years old.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…A Norwegian study reported a 72.8% prevalence of AR and 27.2% of NAR in 10 year-olds 7. A Korean study reported 76.9% AR vs 23.1% NAR 21. The prevalence reported in our study may be different those in from other studies due to not having inhalant allergen test data from all patients, particularly ≤5 years old.…”
Section: Discussioncontrasting
confidence: 81%
“…Sensitization rates to pollen or animal dander increased significantly with advancing age. The prevalence and changing patterns of allergen sensitization in our study are similar to those in other Korean studies 21. Although sensitization to pollen is reported to be related to AR, we did not confirm this finding in our study 3738…”
Section: Discussionsupporting
confidence: 61%
“…Crameri define el ImmunoCAP como la técnica gold standard de diagnóstico in vitro [27], a la espera de nueva evidencia científica respecto al resto de técnicas. Por otro lado, es la técnica de referencia con la que se comparan las demás en los estudios de correlación [28][29][30].…”
Section: Sistemas Multiplexunclassified
“…Chronic rhinitis affects about 30% population worldwide [1]. Allergic rhinitis is one of the most common phenotypes of this disease and one of the most prevalent allergic diseases worldwide [1][2][3][4]. Diagnosis of allergic rhinitis is based on typical clinical signs (rhinorrhea, nasal obstruction or blockage, nasal itching, sneezing, and postnasal drip) and positive results of allergic tests [4].…”
Section: Introductionmentioning
confidence: 99%